Hydroxy-Carboxylic Acid Receptor Actions in Metabolism. (March 2017) - Offermanns, Stefan
Abstract : Lactic acid, the ketone body 3-hydroxy-butyric acid, also known as β-hydroxybutyrate, and the β-oxidation intermediate 3-hydroxy-octanoic acid are hydroxy-carboxylic acids (HCAs) that serve as intermediates of energy metabolism. However, they also regulate cellular functions, in part by directly activating the G protein-coupled receptors HCA1 /GPR81, HCA2 /GPR109A, and HCA3 /GPR109B. During the past decade, it has become clear that HCA receptors help to maintain homeostasis under changing metabolic and dietary conditions, by controlling metabolic, immune, and other body functions. Work based on genetic mouse models and synthetic ligands of HCA receptors has, in addition, shown that members of this receptor family can serve as targets for the prevention and therapy of diseases such as metabolic and inflammatory disorders. Trends: Lactate activates HCA1 on adipocytes in an autocrine manner. It inhibits lipolysis and thereby promotes anabolic effects. Blockade of HCA1 may prevent and treat obesity. HCA2 and HCA3 regulate adipocyte lipolysis and immune functions under conditions of increased FFA formation through lipolysis (e.g., during fasting). HCA2 agonists acting mainly through the receptor on immune cells exert antiatherogenic and anti-inflammatory effects. HCA2 is a receptor for butyrate and mediates some of the beneficial effects of short-chain fatty acids produced by gut microbiota.